Effects of bisphenol A and nanoscale and microscale polystyrene plastic exposure on particle uptake and toxicity in human Caco-2 cells. (September 2020) - Wang, Qiangqiang; Bai, Jialei; Ning, Baoan; Fan, Longxing; Sun, Tieqiang; Fang, Yanjun; Wu, Jin; Li, Shuang; Duan, Chenhui; Zhang, Yingchun; Liang, Jun; Gao, Zhixian
Abstract: Microplastics are abundant in oceans, lakes, soils and even air, and can pose potential threats to human health through food or respiratory intake. Moreover, microplastics have synergistic toxicity to the body after absorbing organic pollutants. In this study, laser scanning confocal microscope and flow cytometry were used to observe the intake of colonic cancer Caco-2 cells to polystyrene plastic with five different particlesizes (300 nm, 500 nm, 1 μm, 3 μm, 6 μm). The uptake rates of microplastics with different particle sizes were 73%, 71%, 49%, 43%, and 30%, respectively. Then, High Performance Liquid Chromatography (HPLC) was used to analyze the adsorption differences of polystyrene plastic with different particle sizes to bisphenol A (BPA). Finally, the proliferation toxicity of polystyrene microplastics with different particle sizeson Caco-2 cells before and after adsorption of BPA was compared. MTT experiments confirmed that microplastics caused an increase in cytotoxicity. This result may be related to increased cellular oxidative stress and mitochondrial depolarization. This hypothesis has been confirmed in reactive oxygen species (ROS) and mitochondrial membrane potential (MMP) assays because nanoscale microplastics cause a large amount of ROS on Caco-2 cells after microplastic exposure, and micron-scale microplastics cause a significant decrease in MMP. At the same time, nanoscale microplastics can cause further depolarization of mitochondria due to their large specific surface area adsorption of BPA, which leads to enhanced cytotoxicity of microplastics after BPA adsorption. The results of this study are of great significance in the evaluation of the safety of microplastics in the human body. Graphical abstract: Image 1 Highlights: The proliferation toxicity of polystyrene microplastics with different particle sizes on Caco-2 cells was analyzed. Microplastics of 300 nm, 500 nm and 6 μm size showed high toxicity to caco-2 cell activity compared with 1 μm and 3 μm. With the increase of microplastics particle size, the oxidative stress in cells decreased. Mitochondrial depolarization induced by microplastics with the size of 6 μm was more obvious than that at 300 nm. The synergistic toxicity of nano-scale polystyrene and bisphenol A on caco-2 cells was more obvious.